Implementasi Metode Bandongan terhadap Pemahaman Siswa dalam Membaca Kitab Kuning di SMK Plus Moch. Luthfi Al-Manan Lombok Timur - Khaerul Umam Fawazi; Rina Dian Rahmawati; Didin Sirojudin (ALSYS, 2025)
This study is motivated by the limited research on the implementation of the bandongan method within formal educational institutions, particularly regarding its effectiveness in enhancing students’ comprehension of kitab kuning. The objective of this study is to examine the implementation of the bandongan method in teaching kitab kuning at SMK Plus Moch. Luthfi Al-Manan, East Lombok, and to analyze its impact on student understanding. This research employs a descriptive qualitative method, with data collected through observation, interviews, and documentation. The findings indicate that the bandongan method aids students in grasping Arabic grammatical structures and the context of classical Islamic scholarship. However, several challenges were identified, including limited interaction, student dependence on teachers, and a lack of instructional media. The study concludes that the bandongan method, when integrated with active approaches such as discussion, can enhance the effectiveness of kitab kuning instruction in formal education. The implications highlight the importance of adapting pesantren methodologies within modern educational systems and underscore the need for teacher innovation in developing strategies for teaching classical religious texts.